Analysis Factor Which Relate With Complaint Musculoskeletal disorders (MSDs) At the Asahan Regency Education Office Employees - Hasibuan, Arini Salsabila; Harahap, Reni Agustina; Utami, Tri Niswati (Indonesian Journal of Medicine, 2025)
Background: One of the major occupational health problems that can arise due to ergonomic risk is musculoskeletal disorders (MSDs). Office workers are among those most susceptible to chronic musculoskeletal health issues. This study aimed to identify factors associated with MSDs among employees of the Asahan District Education Office. Subjects and Method: This study was conducted at the Asahan District Education Office from December to January 2025. A descriptive quantitative analysis using a cross-sectional design was applied. The total population was 71 employees, and total sampling was used. Data were analyzed statistically using the Chi-square test. Results: There were significant associations between age (Mean=1.86; SD=0.350; p=0.004), work duration (Mean=1.65; SD=0.481; p=0.001), BMI (Mean=1.46; SD=0.502; p=0.001), and exercise habits (Mean=1.35; SD=0.481; p=0.001) with MSD complaints. However, gender (Mean=1.39; SD=0.492; p=0.683) was not significantly associated with MSDs. Conclusion: Four factors were significantly associated with MSD complaints. These findings can serve as a reference for institutions to improve ergonomic intervention and prevention efforts, such as mandating employees to participate in morning exercise activities every Friday.